Design of Organic Transformations at Ambient Conditions: Our Sincere Efforts to the Cause of Green Chemistry Practice. Issue 1 (17th November 2015) - Brahmachari, Goutam
Abstract: This account summarizes our recent efforts in designing a good number of important organic transformations leading to the synthesis of biologically relevant compounds at room temperature and pressure. Currently, the concept of green chemistry is globally acclaimed and has already advanced quite significantly to emerge as a distinct branch of chemical sciences. Among the principles of green chemistry, one principle is dedicated to the "design of energy efficiency" – that is, to develop synthetic strategies that require less or the minimum amount of energy to carry out a specific reaction with optimum productivity – and the most effective way to save energy is to develop strategies/protocols that are capable enough to carry out the transformations at ambient temperature! As part of on‐going developments in green synthetic strategies, the design of reactions under ambient conditions coupled with other green aspects is, thus, an area of current interest. The concept of developing reaction strategies at room temperature and pressure is now an emerging field of research in organic chemistry and is progressing steadily. This account is aimed to offer an overview of our recent research works directly related to this particular field of interest, and highlights the green chemistry practice leading to carbon–carbon and carbon–heteroatom bond‐forming reactions of topical significance. Green synthetic routes to a variety of biologically relevant organic molecules (heterocyclic, heteroaromatic, alicyclic, acyclic, etc.) at room temperature and pressure are discussed. Abstract : The design of synthetic protocols for promising and useful organic reactions at ambient conditions coupled with other green aspects is of current interest in the field of green chemistry practice. The present account summarizes our sincere efforts in designing green synthetic protocols for diverse organic transformations at room temperature and pressure reported during the last five years.